Kinetic Study of a Bacterial Cellulose Production by Komagataeibacter Rhaeticus Using Coffee Grounds and Sugarcane Molasses - Souza,Karina Carvalho de (2021)
Abstract Biotechnology can be used to convert waste into valuable products. In this context, there is bacterial cellulose (BC), a natural biopolymer that can be transformed into several useful materials, but its production is limited due to the high cost of the culture media used for its industrialization. In this work, BC was produced from the bacteria Komagataeibacter rhaeticus, using coffee grounds, sugarcane molasses and ethanol. The experiments were carried out under static conditions. The products were collected every 48 h, with a total period of 240 h. The maximum BC production (11.08 g.L-1) was obtained in a culture medium supplemented with coffee powder, hydrolyzed cane molasses and the addition of 1% (v/v) ethanol. The results show that the use of different carbon sources of the evaluated by-products are viable alternatives in reducing costs in BC production.